(untitled) (Fiep Bulletin - online, 2013)
Quality of life at work has never been so mentioned and discussed as it is nowadays. More and more, organizations are looking for new approaches and programs which may promote the physical and psychosocial well-being. Considering that workplace exercise is one of the tools to implement quality of life at work, the outcomes of the research regarding the introduction of these exercises at the Centro Universitário Feevale(RS) are presented. An ex-post-facto study was conducted through data analysis and discussion based on quantitative and qualitative research. Results indicated that the referred program had a positive impact on promoting the collaborators’ quality of life, mainly in respect to the change of life and health habits, and essentially in promoting well-being which was evidenced in 97% of the sampling. There was some interference in the adoption of exercise daily practice, some changes in the relationship among the work teams and a reduction in the pain/discomfort indices. Outcomes for the institution open the way to social responsibility in relation to the institution internal community as one of the best ways to promote the collaborators’ quality of life as well as the corporate image.